Development and Problems of Accounting Higher Education in the U.S. and Bulgaria: Parallels in History - Musov, Michael (Research Papers, 2020)
This paper provides a short historical background of the vocational versus liberal perspectives in accounting higher education. The first section begins with a discussion of the early professionals’ struggle to ensure the status of accounting as a profession and a scholarly discipline in the U.S. The second section discusses some of the perceived problems with accounting education in Bulgaria. Based on the historical parallels outlined, the concluding section suggests three general conclusions.
Keywords: Liberal education; Accounting higher education; Vocational education